USING INQUIRY-BASED TEACHING (5E) IN TEACHING VOCABULARY VIEWED FROM STUDENTSâ LOCUS OF CONTROL - Kayyis, Rahmatika (JURNAL SMART, 2015)
AbstractÂ The objectives of the research are to find out: (1) whether inquiry-based teaching is more effective than grammar-translation method to teach vocabulary; (2) whether the students who have high locus of control have better vocabulary than those who have low locus of control; and (3) whether there is an interaction between teaching methods and locus of control in teaching vocabulary.The factorial design method 2x2 was employed in this research. The population of the research was the students of fourth semester of STKIP Muhammadiyah Pringsewu Lampung in the academic year of 2014/2015. Based on the test of the hypotheses, it can be concluded that inquiry-based teaching is not significant effective method to teach vocabulary. The conclusion is the measurement effectiveness of the method is not determined by the levels of the studentsâ locus of controlÂ Keywords: Vocabulary, Inquiry Based Teaching, Locus of Control